Florid cystitis glandularis (intestinal type) with mucus extravasation: Two case reports and literature review - Zhang, Tao; Yin, Si-Fan; Feng, Wen-Bo; Ke, Chang-Xing (Frontiers in Surgery, 2023)
Cystitis glandularis is a common bladder epithelial lesion characterized by hyperplasia and metaplasia of the bladder mucosa epithelium. The pathogenesis of cystitis glandularis of the intestinal type is unknown and less common. When cystitis glandularis (intestinal type) is extremely severely differentiated, it is called florid cystitis glandularis (the occurrence is extremely rare).